Enzyme Replacement Therapy Ameliorates Multiple Symptoms of Murine Homocystinuria - Majtan, Tomas; Jones, Wendell; Krijt, Jakub; Park, Insun; Kruger, Warren D; Kožich, Viktor; Bassnett, Steven; Bublil, Erez M; Kraus, Jan P (Molecular therapy, 2018)
Classical homocystinuria (HCU) is the most common inherited disorder of sulfur amino acid metabolism caused by deficiency in cystathionine beta-synthase (CBS) activity and characterized by severe elevation of homocysteine in blood and tissues. Treatment with dietary methionine restriction is not optimal, and poor compliance leads to serious complications. We developed an enzyme replacement therapy (ERT) and studied its efficacy in a severe form of HCU in mouse (the I278T model). Treatment was initiated before or after the onset of clinical symptoms in an effort to prevent or reverse the phenotype. ERT substantially reduced and sustained plasma homocysteine concentration at around 100 μM and normalized plasma cysteine for up to 9 months of treatment. Biochemical balance was also restored in the liver, kidney, and brain. Furthermore, ERT corrected liver glucose and lipid metabolism. The treatment prevented or reversed facial alopecia, fragile and lean phenotype, and low bone mass. In addition, structurally defective ciliary zonules in the eyes of I278T mice contained low density and/or broken fibers, while administration of ERT from birth partially rescued the ocular phenotype. In conclusion, ERT maintained an improved metabolic pattern and ameliorated many of the clinical complications in the I278T mouse model of HCU.
Keywords: oxidační stres; modely nemocí na zvířatech; Glucose; polyethylenglykoly; cystathionin-beta-synthasa; fenotyp; Cystathionine beta-Synthase; Phenotype; preklinické hodnocení léčiv; alopecia; inborn error of metabolism; preclinical studies; eye defect; metabolomics; homocysteine; glukosa; bone density; metabolismus lipidů; aminokyseliny sírové; Polyethylene Glycols; Animals; játra; Drug Evaluation, Preclinical; zvířata; Lipid Metabolism; Disease Models, Animal; enzymová substituční terapie; myši; PEGylation; enzyme replacement; Liver; Mice; Oxidative Stress; cystathionine beta-synthase; homocystinurie; Enzyme Replacement Therapy; Homocystinuria; Amino Acids, Sulfur